RANCANG BANGUN WIRELESS SENSOR NETWORK UNTUK MONITORING SUHU DAN KELEMBABAN PADA LAHAN TANAMAN JARAK - Pambudi, Kusbiono Wisnu; Jusak, Jusak; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
One source of vegetable oil highly prospective to be used as raw material for biodiesel is Jatropha curcas nkL. But to get the maximum oil content of Jatropha, takes temperature and soil moisture are controlled continuously. Because it takes a tool for monitoring crop. In this final project used technology Wireless Sensor Network ( WSN ). WSN is a wireless network consisting of multiple sensors that work together to monitor physical and environmental conditions. Thus supporting the sensor devices can facilitate monitoring temperature and humidity in the soil around the plant plantations distance.WSN communication protocol testing, showed that the sending or receiving data in accordance with the address of the destination node and 100meter range of reach. The average percentage error in moisture sensor node1 is 4% and node2 is 5.1%, the temperature sensor node is 0.43% and node is3.87% . While in the process of data validation, 95% of the system works well.